'Any room won't do.' Clinical psychologists' understanding of the consulting room. An interview study. Issue 4 (2nd October 2018) - Punzi, Elisabeth; Singer, Christoph
Abstract : In the social sciences, there is increasing interest in spatial practices and the meaning of places. The meaning of the psychotherapeutic room and its boundaries has traditionally been underlined in psychodynamic practice. In this study we investigated how clinical psychologists, working from different perspectives and with varying interventions and populations understand and use the consulting room. Five clinical psychologists were interviewed about how they perceive and use consulting rooms. The interviews were analysed using Interpretative Phenomenological Analysis. The participants understood the consulting room as a logistic unit but also as a welcoming place for relational encounters and sensed that spatial stability was important for their capacity to be fully attentive to their clients. Moreover, technological booking systems could hinder clinical work. The results were understood with respect to Winnicott's theories of transitional space and holding. In sum, the importance of the room does not seem to be of concern exclusively to psychodynamic psychologists. On the contrary, it seems as if psychologists working with varying interventions and from different perspectives emphasise stable and personal consulting rooms that permit them to adapt to the needs of the clients, be attentive, and avoid disturbances.